Tuto(k) the role of Universal Design for Learning (UDL) in creating innovative learning environments for Filipino learners - Ditan, Angelica M.
Education for all is a basic precept of Philippine Education policy. Filipino children must have an equal right to education regardless of where they live, gender, social and cultural background or any special needs. Unfortunately, the current design of learning environment in the Philippines is not fully optimized to make learning accessible to all types of learners, especially children with disabilities (CWDs). Universal Design for Learning (UDL) is a newly emerging and promising practice to pedagogy that can respond to that challenge in education in the Philippines. The most important feature of UDL-make learning more accessible and appropriate for all types of learners. With the use of appropriate and effective goals, UDL inspired learning landscapes can be designed to increase flexibility and ultimately, reduce barriers to learning.